PS-B06-11: GLUCAGON-LIKE PEPTIDE-1 SUPPRESSES ACTIVATED EFFECTOR MEMORY T CELL SUBSETS IN THE FATTY LIVER INDUCED BY ANTI-CD3-ADNTIBODY ADMINISTRATION IN LEAN MICE. (January 2023) - Itoh, Arata; Yuki, Kazunari; Irie, Junichiro; Itoh, Hiroshi
Abstract : Objective: We previously invented a disease-model of hepatosteatosis, glucose tolerance and hyperlipidemia, typically observed in non-alcoholic fatty liver disease with metabolic syndrome, but without obesity, through activation of CD4-positive lymphocytes by anti-CD3 antibody administration in lean mice. We also showed that this model is CD4 T-cell dependent and glucagon-like-protein-1 receptor agonist reduces cytokine production in the liver with amelioration of fatty liver, hyperglycemia and hyperglycemia in this model. The precise mechanisms, however, remains unclear. We investigated how GLP-1RA targets and suppresses T cells. Design and Method: GLP-1R expression on activated T cell subsets in the liver and spleen was analyzed using flow-cytometry one day after administration of anti-CD3 antibody in the female lean Balb/c mice. Purified splenic CD4 T cells were differentiated into Th1, Th2, Th17 or regulatory T cells in-vitro and glp1r gene expression and GLP-1R protein expression were analyzed with real-time PCR and flow-cytometry, respectively. Results: anti-CD3 antibodies significantly increased GLP-1R+ CD62L- CD44+ effector-memory CD4 and CD8 T cells in the liver and GLP-1RA protected from increasing number of those CD4 and CD8 T cells in the liver in vivo. Activated and in-vitro induced Th1, Th2, Th17 and regulatory T cell subsets expresses express GLP-1R. Conclusions: GLP-1RA targets activated/effector-memory T cell subsets and reduces their proliferation and cytokine production.